Comportamento hidráulico de um sistema de wetlands construídos de escoamento vertical (primeiro estágio do sistema francês) - Mirene Augusta de Andrade Moraes (2019)
The French System (SF), a variant of vertical flow constructed wetlands (VFW), receives raw sewage and is classically composed of three filters in parallel, with alternating phases of feeding and rest. A complicator of VFW is that it is governed by the conditions of the unsaturated media, adding complexity because it is very dynamic. This work was developed in the CePTS UFMG / COPASA and had as objective to contribute to a better understanding of the hydraulic behavior in terms of influent distribution, percolation in the porous medium and effluent collection from a system constituted by the first stage of SF operated with only two units and an extended feeding cycle (seven days). Monitoring of the outflow and the parameters TSS, electric conductivity, redox potential, DO and pH were carried out in the treated effluent collection channel. To obtain the residence time distribution (RTD) curves, the tracer used was the 99mTc. In addition, several models were evaluated: Gamma – tanks in series (NTIS), log-normal distribution, Vasel and Schrobiltgen axial dispersion, Vasel and von Sperling compartmentalized and analytical solution of the Richards equation proposed by Mannich and Guetter. It was observed that, at the beginning of the seven day feed cycle, the system required time to soak and retain moisture. From the middle to the end of the feed cycle, the system increased the internal storage of the liquid volume, probably due to a reduction in the hydraulic conductivity of the filter. The sludge deposit has a primordial function in the FS operation, and it seemed to hinder the passage of the liquid and the DO transfer. The RTD results confirmed these trends. The 99mTc represented well the system’s behavior when associated to a complexant such as DMSA, and could therefore be pointed as a promising tracer in the study of VFW. The quality parameters of the treated effluent were related to the effluent hydrograph, which could also indicate the behavior of other parameters not analyzed. It is concluded that in unsaturated and batch systems, such as VFW, the tracer can be considered the liquid itself. Thus, the effluent hydrograph has much to show about the system’s hydrodynamics. The Gamma - NTIS distribution was not very adequate for the representation of this FS, since it was unable to adjust the peak flows. The Log-normal distribution, on the other hand, exhibited good correlations between the measured and estimated data. In relation to the models of axial dispersion and compartmental, they also demonstrated good adherence to field data. However, the analysis of these models can not be done customarily. A model developed in Excel was tried based on an analytical solution of the Richards equation. But the adjustment was not appropriate, demonstrating the need for adaptations. It is suggested that further studies should be carried out under similar hot weather conditions in order to better understand the hydraulic operation of the FS with less parallel units and different feeding and rest cycles. Emphasis is given to the need for research to improve filter hydraulics and to develop simplified models applied to unsaturated media.